2004
DOI: 10.1101/gad.1221804
|View full text |Cite
|
Sign up to set email alerts
|

MIM/BEG4, a Sonic hedgehog-responsive gene that potentiates Gli-dependent transcription

Abstract: Sonic hedgehog (Shh) signaling plays a critical role during development and carcinogenesis. While Gli family members govern the transcriptional output of Shh signaling, little is known how Gli-mediated transcriptional activity is regulated. Here we identify the actin-binding protein Missing in Metastasis (MIM) as a new Shhresponsive gene. Together, Gli1 and MIM recapitulate Shh-mediated epidermal proliferation and invasion in regenerated human skin. MIM is part of a Gli/Suppressor of Fused complex and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 37 publications
6
135
0
3
Order By: Relevance
“…MTSS1, whose expression is down-regulated or absent in several metastatic cell lines (Nixdorf et al 2004, Loberg et al 2005, is a sonic hedgehog responsive actin binding protein involved in the regulation of actin filament assembly and is a potentiator of Gli-dependent transcription (Callahan et al 2004). Interestingly, MTSS1 was transiently up-regulated in the granulosa layer of bovine follicles at 12 h post-GnRH injection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MTSS1, whose expression is down-regulated or absent in several metastatic cell lines (Nixdorf et al 2004, Loberg et al 2005, is a sonic hedgehog responsive actin binding protein involved in the regulation of actin filament assembly and is a potentiator of Gli-dependent transcription (Callahan et al 2004). Interestingly, MTSS1 was transiently up-regulated in the granulosa layer of bovine follicles at 12 h post-GnRH injection.…”
Section: Discussionmentioning
confidence: 97%
“…CD36 is a multifunctional scavenger receptor that binds known autocrine growth factors that can regulate cell growth, adhesion, and angiogenesis (Febbraio et al 2001). MTSS1 is a sonic hedgehog responsive actin binding protein (Callahan et al 2004) and a functional hedgehog signaling system in murine follicles has been reported (Wijgerde et al 2005, Russell et al 2007. TFG is involved in promoting NF-kappaB activity (Miranda et al 2006), which is potentially related to cumulus expansion in mice (Takahashi et al 2006).…”
Section: Gonadotropin Surge Induced Up-regulation Of Gene Expression mentioning
confidence: 99%
“…Positive regulators of Gli function have also been found, including the kinase Dyrk1 [87] and the actin-binding protein Missing in metastasis (MIM, also called BEG4) [88]. Others include peptide-growth factor (PGF)-activating receptor tyrosine kinases, such as EGF, PDGF, FGF and IGF, which synergize with or affect Hh-Gli function [21,48,56,57,89].…”
Section: Box 2 the Gli Code Is Regulated Exquisitely By Multiple Mechmentioning
confidence: 99%
“…K17 is a known target of Hh signaling (24), and expressing the constitutively active SmoM2 allele to activate Hh signaling in the epidermis causes K17 expression and epidermal thickening (25), recapitulating aspects of the touch dome microenvironment. To test if Hh activation is sufficient to drive Merkel cell production or expansion in the epidermis, we used adult K14-CreER;R26 SmoM2/+ mice (n = 8) to activate the Hh signaling pathway in epidermal keratinocytes.…”
Section: Activation Of Shh Signaling Is Not Sufficient To Establish Omentioning
confidence: 99%